2019
DOI: 10.1371/journal.pone.0220841
|View full text |Cite
|
Sign up to set email alerts
|

Plasma neutrophil gelatinase-associated lipocalin levels are associated with the presence and severity of coronary heart disease

Abstract: Objective This study aimed to compare the levels of plasma neutrophil gelatinase-associated lipocalin (NGAL), matrix metalloproteinase (MMP)-9, high-sensitivity C-reactive protein (hs-CRP), and interleukin (IL)-1β across different clinical presentations of coronary artery disease and to evaluate the relationship between those biomarkers and the severity of coronary artery lesions in patients without kidney disease. Methods We examined 365 eligible patients who underwent… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
14
1
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 19 publications
(17 citation statements)
references
References 34 publications
1
14
1
1
Order By: Relevance
“…These variants are overexpressed in crucial steps of embryonic cardiovascular development, are virtually absent in healthy adult organs, and are abundantly re-expressed in a wide range of cardiovascular diseases [20][21][22][23][24]28,32,33]. NGAL, classically known as a biomarker of renal failure, could be evidenced as a useful circulating reflector of cardiovascular inflammation, including atherosclerosis development [17,34]. In accordance, we could show significantly elevated levels in AS patients compared to controls.…”
Section: Discussionsupporting
confidence: 79%
“…These variants are overexpressed in crucial steps of embryonic cardiovascular development, are virtually absent in healthy adult organs, and are abundantly re-expressed in a wide range of cardiovascular diseases [20][21][22][23][24]28,32,33]. NGAL, classically known as a biomarker of renal failure, could be evidenced as a useful circulating reflector of cardiovascular inflammation, including atherosclerosis development [17,34]. In accordance, we could show significantly elevated levels in AS patients compared to controls.…”
Section: Discussionsupporting
confidence: 79%
“…LDL-C, ApoB and SYNTAX scores were significantly positively correlated, which is also consistent with previous research [ 36 ]. However, studies have shown that hs-Crp also correlates positively with CHD severity [ 37 ], which does not agree with results in the present study for patients with PMI. According to these findings, it suggests that severe coronary lesions in various types of CAD (e.g., ST-segment elevation myocardial infarction, stable angina pectoris) may be associated with different predictors.…”
Section: Discussioncontrasting
confidence: 99%
“…Plasma NGAL levels are significantly higher in STEMI patients than in the stable angina pectoris patients and control subjects [ 85 ]. Multivariate regression analysis presented that NGAL levels were independently correlated to SYNTAX scores [ 85 ]. Plasma NGAL showed a better ability in discriminating severe coronary disease than MMP-9, hs-CRP, and IL-1β [ 85 ].…”
Section: Neutrophil Gelatinase-associated Lipocalin (Ngal)mentioning
confidence: 99%